"Access to Research": how UK public libraries are offering access to over 15 million academic articles for free. Issue 2 (16th May 2016) - Griffin, Jonathan
Abstract : Purpose: The purpose of this study is to describe a unique service offering by UK public libraries that provides access to over 15 million academic articles for free. Design/methodology/approach: The approach is descriptive. Findings: The service has been a success with users, but more training for staff, as well as promotion, is needed. Social implications: The study will be potentially important for enabling access to a vast amount of published academic articles for a wide section of UK citizens. Originality/value: The first article on this service is aimed specifically at the LIS community.